THE IMPACT OF CAPITAL FLOWS ON THE REAL EXCHANGE RATE: EVIDENCE FROM SERBIA - Zdravkovic, Aleksandar; Bodroža, Duško; Jovičić, Elena (The European Journal of Applied Economics, 2026)
As a small open economy increasingly integrated into global financial markets, Serbia is exposed to fluctuations in cross-border capital movements that may influence exchange rate dynamics and macroeconomic stability. This paper examines the relationship between international capital flows and the real effective exchange rate in Serbia, with particular attention to the structure of capital inflows. The structural vector autoregression (SVAR) model is applied to capture the dynamic interactions between external economic conditions, capital flows, monetary policy, domestic economic activity, and the real effective exchange rate, using quarterly data for the period from 2007 to 2024. The results, obtained through impulse response analysis, indicate that shocks to capital inflows lead to a moderate appreciation of the real exchange rate, although the magnitude and persistence of the effect vary depending on the composition of capital flows. Equity inflows show a somewhat more persistent appreciation effect compared with debt inflows, while the overall impact of total capital flows appears relatively limited. These findings highlight the importance of capital flow composition for exchange rate dynamics and provide useful insights for the design of exchange rate and macroprudential policies in small open economies.
Keywords: Capital flows, Real effective exchange rate, Small open economy, Serbia, Vector autoregression